EFFECT OF COPPER ADDITION TO ELECTRICAL CONDUCTIVITY AND ELECTROCHEMICAL PROPERTIES OF REDUCED GRAPHENE OXIDE (RGO) - BITYASMAWAN ABDILLAH (NIM: 10213057), OKTAVIARDI
Graphene is a two-dimensional material which has interesting properties such as high theoretical surface area, excellent intrinsic strength, thermal, and electrical conductivity properties. There are several methods to synthesize graphenes, such as micromechanical exfoliation, epitaxial growing, chemical vapor deposition, and reduction of graphene oxide (GO). Among these methods, chemical reduction of GO has been preferred due to higher yield product and possibility in large-scale production. However, the remaining oxygen functional group after reduction process of graphene oxide could resist electron transport. Thus electrical conductivity and electrochemical properties of rGO is lower than pristine graphene. Therefore, in this research, we introduced copper to enhance electrical conductivity and electrochemical properties of rGO, since copper has excellent conductivity properties. rGO/Cu has successfully in-situ synthesized via microwave assisted. The resulting samples were characterized by using X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), Raman spectroscopy, four-point probe, and Electrochemical Impedance Spectroscopy (EIS). The highest conductivity value of 24.85 S/cm was obtained in rGO/Cu 1 wt% sample treated with annealing at 300 Ã‚Â°C for 45 minutes. Annealing treatment could increase the electrical conductivity of the sample. Cu2O were found by XRD characterization of rGO/Cu 5wt% could lead to decreasing of electrical conductivity in the sample which added by Cu more than 1 wt%. Electrochemical properties of samples have been characterized using Electrochemical Impedance Spectroscopy (EIS), resulting in charge transfer resistance (Rct) value of RGO/Cu 1 wt% sample is 2.906 ohm.